Peningkatan Keterampilan Mahasiswa dalam Mempublikasikan Artikel Dalam Jurnal Terakreditasi Sinta - Ekaputra, Firdiawan; Hendra , Hendra (Pendidikan Sejarah FKIP Universitas JAMBI, 2023)
This training aims to improve student skills in publishing articles in sinta accredited journals. The training activities were attended by students of the Chemistry Education Study Program, Jambi University, semester 6, totaling 26 people. Training activities were held in room L-102 FKIP Jambi University on May 9, 2023. The implementation of training activities consists of three stages of training activities, namely the preparation stage, implementation stage, and evaluation stage. The preparation stage consists of problem analysis activities, determining training methods, and preparing training materials. The implementation stage included the delivery of training materials, demonstration of the use of the Sinta website, and discussion activities. Evaluation activities are carried out to determine the achievement of training activities that have been carried out. Based on the results of the evaluation of training activities to improve student skills in publishing articles to sinta accredited journals, there was an increase in competence in finding references to sinta accredited articles and publishing articles in sinta accredited journals. The achievement of the implementation of training activities obtained a score of 4.34 which was classified as a very good category.